Introducing Music and Movement-Based Self-Therapy for Children with Cerebral Palsy During the Covid-19 Pandemic - Zayinna Syarifatunnisaa; Alliya Tsabita Zahra; Indy Ratna Pratiwi; Lathifah Indah Nurazizah; Rika Aprilia Budiman; Leli Kurniawati (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to socialize an independent therapy program for parents of children with cerebral palsy. Self-therapy can be done at home using simple tools. In practice, this research conducts training through workshops and webinars. The workshops and webinars discussed the implementation of self-therapy and the use of maracas as a simple therapeutic tool. The method used is a qualitative method with a descriptive qualitative approach. The results of this study were reviewed from discussion data and interviews with the management and chairman of the Ramah Cerebral Palsy Bogor Foundation, that music-based self-therapy is easy to apply during a pandemic. Based on the research that has been done, music, motion, and song therapy are an effort to stimulate the development of motor aspects in children with cerebral palsy. This independent therapy based on music, motion, and song needs to be applied consistently to reduce wilting and stiffness in children.